Vladimir Mikhailovich Zhukovsky - Chimica Techno Acta Editors (Chimica Techno Acta)
This issue consists of the articles written by renowned experts in the field of solid state chemistry from Ekaterinburg, Novosibirsk, Ulan-Ude and St. Petersburg, and is dedicated to the memory of Vladimir Mikhailovich Zhukovsky, who remains an example for us in science and life.